2016
DOI: 10.1002/jat.3303
|View full text |Cite
|
Sign up to set email alerts
|

Copper toxicology, oxidative stress and inflammation using zebrafish as experimental model

Abstract: Copper is an essential micronutrient and a key catalytic cofactor in a wide range of enzymes. As a trace element, copper levels are tightly regulated and both its deficit and excess are deleterious to the organism. Under inflammatory conditions, serum copper levels are increased and trigger oxidative stress responses that activate inflammatory responses. Interestingly, copper dyshomeostasis, oxidative stress and inflammation are commonly present in several chronic diseases. Copper exposure can be easily modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 108 publications
(202 reference statements)
8
107
0
1
Order By: Relevance
“…While under most cellular conditions Cu(I) levels are tightly controlled and free Cu(I) concentrations are very low, 62 several disease states are characterized by misregulation of cellular copper. 56,73,8791 A clear understanding of Cu(I) binding to Zn(II)-metalloproteins is important in identifying putative targets for disruption by Cu(I) under conditions of copper misregulation. Previous work has shown that the ZF-based Sp1 transcription factor regulates the expression of multiple copper-binding proteins in response to fluctuations in copper concentrations, and it is hypothesized that the ZFs in Sp1 function as intracellular copper sensors via copper interaction at the zinc binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While under most cellular conditions Cu(I) levels are tightly controlled and free Cu(I) concentrations are very low, 62 several disease states are characterized by misregulation of cellular copper. 56,73,8791 A clear understanding of Cu(I) binding to Zn(II)-metalloproteins is important in identifying putative targets for disruption by Cu(I) under conditions of copper misregulation. Previous work has shown that the ZF-based Sp1 transcription factor regulates the expression of multiple copper-binding proteins in response to fluctuations in copper concentrations, and it is hypothesized that the ZFs in Sp1 function as intracellular copper sensors via copper interaction at the zinc binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…68,7072 The two CCCH domains must be bound to zinc (or iron) and folded in order for the protein to bind to mRNA. 1,44 There is evidence that Cu(I) levels are elevated during inflammation, 73,74 suggesting that Cu(I) may target TTP and affect its function, making it a particularly relevant ZF to utilize for studies aimed at understanding how Cu(I) can target ZF sites. We prepared a single- and double-domain construct of TTP, called TTP-1D and TTP-2D, and measured the structural and, for TTP-2D, the functional affects of Cu(I) binding.…”
Section: Introductionmentioning
confidence: 99%
“…(); Song et al ., ; Ahamed et al ., ). CuO NPs also exhibit neurotoxicity and genotoxicity in vivo , and ROS generation was suggested to be the reason for the induction in toxicity (Pereira et al ., ).…”
Section: Cuo Nps‐induced Toxicity In Vivomentioning
confidence: 97%
“…Cu ion may also play a protective role in the accumulation of human islet amyloid peptide, which is the major component of amyloid deposits in pancreatic β-cells of type 2 diabetic patients; however, whether or not Cu have a protective role in the etiology of type 2 diabetes is not clarified (19, 20). Excess of Cu under inflammatory conditions trigger oxidative stress which are present in chronic diseases (21). On the other hand, increased Zn ion levels may provide a protective effect against Cu toxicity by competing for Cu binding sites (16).…”
Section: Introductionmentioning
confidence: 99%